Effect of Araxá rockphosphate and simple superphosphate on some physiochemical properties and on the available residual P of an Oxic Paleudalf - C., Segundo Urquiaga; Reichardt, K.; Libardi, P.L (Pesquisa Agropecuaria Brasileira, 2014)
The experiment was developed using surface soil samples (TRE, Oxic Paleudalf) from the Experimental Field Station of ESALQ, located in Piracicaba, SP, Brazil. This soil had received during the period al three years 6 ton/ha of Araxá rockphosphate (34,6% P2O5) or 1,2 ton/ha of simple superphosphate (20% P2O5) while three crops of beans (Phaseolus vulgaris, L.) were grown. This greenhouse experiment had the objective of evaluating the effect al these fertilizer applications on some physico-chemical properties of the soil, and also study the residual P effect through the Olsen and "A" value methods. Results indicate that Araxá rockphosphate (48.4% CaO), although applied at high rate, did not affect soil reaction. On the other hand, both fertilizers increased the exchangeable Ca2+ level approximately 0,5 mE/100 g. In short term (less than three years), the response of Araxá rockphosphate corresponded to its 2% citric acid soluble P2O5, content (4%) rather than to its total P2O5 content. Through "A" values (using KH232PO4) it was shown that the residual effect of simple superphosphate (108.6 kg P2O5/ha) was similar to the Araxá rockphosphate (136.6kg P2O5/ha), but these were significantly greater than the natural P content of the soil (54.0 kg P2O5/ha). The evaluation of available P in the soil (with and without fertilizer) by Olsen's method, had an efficiency of 64 and 94% (respectively) as compared to the "A" value method.